Science Process Skills in Implementation Food Test Practicum in Junior High School - Desi Yulihapsari; Sofyan Anif; Ahmad Muhibbin (Jurnal Penelitian Pendidikan IPA, 2023)
Science process skills are one of the components of psychomotor competence, these skills can support student activities to acquire knowledge. In learning activities having science process skills is something that is very important for students. This study aims to measure and find out the concept of applying and understanding science process skills in the science learning process, especially in food testing practicum. This type of research on food test material is qualitative descriptive research. The research was conducted on class VIII students of SMP Muhammadiyah Al-Kautsar PK Kartasura Sukoharjo. In this study, there were two data that were examined, namely the first data from the results of student science process skills observations. The research was conducted through three stages, namely pre-survey, implementation, and drawing conclusions. The second data collection was based on the teacher's knowledge of science process skills and the approach to the science teaching process by using interview techniques with science subject teachers in schools. The data obtained from the research were analyzed using quantitative and qualitative methods. The data shows that the overall understanding and application of students' science process skills based on the results of observations shows a good category, namely 76.3%. The conclusion drawn is that the science process skills approach to SMP Muhammadiyah Al-Kautsar PK students is in a good category. Based on the results of interviews with science teachers, the results show that so far, the lecture method is the method most often encountered and implemented by teachers in learning science. In fact, the implementation of science practicum is very important. In the practicum method, it is hoped that students will be able to interact directly with objects as well as be able to empower various competencies, especially being able to develop science process skills